2000
DOI: 10.1021/ie0005304
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Depolymerization of Poly(ethylene terephthalate) in a Potassium Hydroxide Solution

Abstract: The depolymerization of poly(ethylene terephthalate) (PET) flakes in a potassium hydroxide solution was carried out in a stirred batch reactor at 120, 140, and 160 °C, below its melting point and under pressures of about 1.7, 2.9, and 4.6 atm, respectively. After the reactions, the residual solids almost remained in flake shape and their molecular weights were close to that of PET before the reaction. The products composed of ethylene glycol and terephthalic potassium salt were in the liquid phase. They were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
7

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(60 citation statements)
references
References 12 publications
4
49
0
7
Order By: Relevance
“…The activation energy for the alkaline hydrolysis of PET calculated from the slope was 68±2 kJ mol -1 . This value is in fairly good agreement with 69 kJ mol -1 reported by Wan et al [9] for the alkaline depolymerisation with potassium hydroxide. Further, this activation energy value was quite lower than the corresponding value observed for acid hydrolysis, 100-110 kJ mol -1 [10,11].…”
Section: Non-catalysed Alkaline Hydrolysis Of Petsupporting
confidence: 92%
See 1 more Smart Citation
“…The activation energy for the alkaline hydrolysis of PET calculated from the slope was 68±2 kJ mol -1 . This value is in fairly good agreement with 69 kJ mol -1 reported by Wan et al [9] for the alkaline depolymerisation with potassium hydroxide. Further, this activation energy value was quite lower than the corresponding value observed for acid hydrolysis, 100-110 kJ mol -1 [10,11].…”
Section: Non-catalysed Alkaline Hydrolysis Of Petsupporting
confidence: 92%
“…Within the context of alkaline hydrolysis of PET a potentially active PTC should efficiently transport the hydroxide anion from the aqueous phase to the organic phase (solid PET), thereby increasing the reaction rate. Recent studies have only evaluated the role of quaternary ammonium salts [ 1 [2][3][4][5][6][7][8][9][10][11][12][13][14]; however, no attention has been paid to examining the behaviour of tetralkyl phosphonium salts as PTCs (table 1) for this specific reaction system. For this screening study the following operating conditions were used: stirring rate 400 rpm, particle size 250 µm, inert atmosphere 200 kPa N 2 , temperature 80 ºC, NaOH concentration 1.67 mol l -1 , PET concentration 0.29 mol l -1 , and PTC concentration 0.07 mol l -1 .…”
Section: Alkaline Hydrolysis Of Pet Assisted By Phase Transfer Catalystsmentioning
confidence: 99%
“…The yields (%) of monomers are almost equal to PET conversion [13±16]. Kinetic studies of PET depolymerization were conducted [6] but the rates found were very low and did not meet the requirements of the industrial depolymerization process. In the past no detailed data were available about product characterization and kinetics, necessary to strengthen the explanation of alkali depolymerization of PBT.…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, a reatividade é acentuadamente aumentada, diminuindo o tempo de reação na ordem de 24 a 48 horas se a hidrólise for conduzida em temperaturas próximas ou superiores à fusão do poliéster, e obviamente neste caso, sob elevados valores de pressão [13] . Toda esta análise mostra que uma possível reação de hidrólise na matriz de policarbonato, cuja temperatura de transição vítrea é da ordem de 150 °C, enquanto que a temperatura de deflexão ao calor sob carga está na faixa de 130 °C; se ocorrer deverá ser muito lenta à temperatura ambiente, porém possivelmente dependente da alcalinidade do meio e do histórico de processamento do material em termos de nível de concentração de tensões internas congeladas.…”
Section: Figuraunclassified
“…Já no segundo caso, e em função da polaridade relativa da matriz polimérica, a interação da água com grupos polares da matriz pode atingir níveis tais que sua difusão na fase volume da matriz polimérica permita sua localização em espaços localizados nas regiões intra e supra macromoleculares e como conseqüência, pode-se observar um fenômeno de antiplasticização [13,16] .…”
Section: Ensaio De Traçãounclassified